Perpetual Peace Models: An Analysis of Their Inadequacies - Pratap, Bhanu (Kathmandu School of Law Review, 2025)
The relativist nature, cultural specificity and a priori approach to Peace Models make them tumultuous in the perspective of international law. A legal positivist’s understanding of peace implies that it is a status akin to war, and construing it in philosophical terms yields absurdity. An argument will be made that European thinkers have dominated the field of Perpetual Peace Models, thereby eclipsing Buddhist and Islamic ones. The claim of an alleged ‘universal’ peace is a European affair that undermines the complex and nuanced nature of peace. Apart from its unidimensional European perspective, peace models have various factual infirmities—they fail to consider the status of neutrality, a legal device used by European countries to restrict the theatre of war; and they are moral axioms that fail to account for the complex nature of peace treaties. Peace treaties, which are only peaceful in name, also fail to reflect the inequality among the State parties. As the victor usually positions itself as the dominant actor in peace treaties, it dwarfs the defeated party’s negotiating capacity. For instance, the Covenant of the League of Nations, though a part of Wilson’s foreign policy, contained clauses that institutionalised imperialism and rejected sovereign equality in the most blatant manner possible. Historically, the Kantian Peace model, though popular, is inconsistent with the Charter of the United Nations. Medieval peace models fail to consider the organic nature of peace. Peace in the 21st century is not merely the absence of war, but also the defence of self-determination, the protection of refugee rights, the institutionalisation of transitional and post-conflict justice, the upholding of human rights, and the observance of laws related to war. These added dimensions of peace make perpetual Peace Models a minimalist device for settling disputes. A curious case of peace formation is Japan, which adopted a pacifist constitution in 1945 under the influence of the USA, which was its Occupying Power. Article 9 of the 1945 Constitution made it unconstitutional for the Japanese to maintain an army. To circumvent this rigid provision, the Japanese government formed the Special Defence Force, which can be considered a legislative manoeuvre, and the Japanese Courts have questioned its constitutionality. The Japanese Constitutional Peace process raises specific questions of interest. Was the Japanese Constitution of 1945 an exercise of free will, as it was drafted under the influence and supervision of the USA as an occupying power? Has Article 9 and the Special Defence Forces created a curious conundrum in which the nature of peace itself has become a battleground between the legislature and the judiciary? This article explores such questions.